2001
DOI: 10.1177/136346150103800103
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Post-Natal Depression, Somatization and Behaviour in Malaysian Women

Abstract: This study evaluated the rate of post-natal depression (PND) in a Malaysian population, investigated the relationship between belief systems and PND, and examined the relationship between PND and somatization. The sample included 154 consecutive attendees for a 6-week post-natal check at a general hospital well-baby clinic in Kuala Lumpur. Patients were assessed using the Edinburgh Post-Natal Depression Score (EPNDS), the Bradford Somatisation Inventory (BSI), and a questionnaire to assess beliefs about pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 5 publications
(5 reference statements)
2
24
2
Order By: Relevance
“…There was no relationship found between their new mothers' mood and the practicing of postpartum ritual. Other Asian studies have reported similar findings (Yamashita, Yoshida, Nakano, & Tashiro, 2000;Grace, Lee, Ballard, & Herbert, 2001). Huang and Mathers (2001) reported a high prevalence of postnatal depression (PND; 19%) among 101 postpartum Taiwanese despite the fact that 72%-95% of them practiced the Chinese postpartum ritual.…”
Section: Stressful Postpartum Periodsupporting
confidence: 52%
“…There was no relationship found between their new mothers' mood and the practicing of postpartum ritual. Other Asian studies have reported similar findings (Yamashita, Yoshida, Nakano, & Tashiro, 2000;Grace, Lee, Ballard, & Herbert, 2001). Huang and Mathers (2001) reported a high prevalence of postnatal depression (PND; 19%) among 101 postpartum Taiwanese despite the fact that 72%-95% of them practiced the Chinese postpartum ritual.…”
Section: Stressful Postpartum Periodsupporting
confidence: 52%
“…This fact probably reflects the reduced awareness of society towards the seriousness of the disease. The prevalence of the disease in South and East Asia, ranges between 12.7 and 17.3 % in China [2], 22.35 % in Indonesia [50], between 13.5 and 73.7 % in Taiwan [32,51], 0.5-6.8 % in Singapore [31,52], 16.8 % in Thailand [53], 33 % in Vietnam [2], 4.9 % in Nepal [54], 3.9-9.8 % in Malaysia [55,56], 22 % in Jordan [4] and between 11 and 32.4 % in India [2,57].…”
Section: Ppd In East and South Asiamentioning
confidence: 99%
“…In Malaysia, a somatic symptom scale was strongly correlated with postnatal CMD (Grace et al, 2001). Perinatal CMD in LAMIC settings has been associated with impaired functioning (Patel et al, 2002), which has, in turn, been hypothesised to be associated with reduced help-seeking of the mother on behalf of her child (Rahman et al, 2004) and a range of poorer child health outcomes (Anoop et al, 2004; Patel et al, 2003; Rahman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%